Advances in Signal Processing and Communication Select Proceedings of ICSC 2018 - Rawat, Banmali S.; Trivedi, Aditya; Manhas, Sanjeev; Karwal, Vikram (Lecture Notes in Electrical Engineering,, 2019)
This book is a collection of selected peer-reviewed papers presented at the International Conference on Signal Processing and Communication (ICSC 2018). It covers current research and developments in the fields of communications, signal processing, VLSI circuits and systems, and embedded systems. The book offers in-depth discussions and analyses of latest problems across different sub-fields of signal processing and communications. The contents of this book will prove to be useful for students, researchers, and professionals working in electronics and electrical engineering, as well as other allied fields. .